Fresh Frozen Plasma Transfusion: An Independent Risk Factor for Hemodynamically Significant Patent Ductus Arteriosus in Premature Infants - Huang, Chun-Pin; Hung, Yi-Li; Hsieh, Wu-Shiun; Shen, Chung-Min (American Journal of Perinatology, 2021)
Objective The incidence of patent ductus arteriosus (PDA), a major complication of prematurity, may be reduced by restricting fluid administration. Prophylactic fresh frozen plasma (FFP) transfusion may reduce the incidence of intraventricular hemorrhage in these infants, but risks transfusion-related volume overload. We conducted a retrospective study to investigate whether FFP transfusion is a risk factor for hemodynamically significant PDA (hsPDA) in very low birth weight (BW) premature infants.Study Design From January 2009 to December 2014, 102 premature infants with gestational age (GA) less than or equal to 30 weeks were admitted to a level III neonatal intensive care unit, and 88 patients were enrolled. Patients were further divided into non-hsPDA (n = 29) and hsPDA groups (n = 59). We retrospectively reviewed demographic characteristics and various perinatal and postnatal variables. Univariate and multivariable analyses were performed to identify risk factors for hsPDA.Results Compared with non-hsPDA patients, hsPDA patients had lower mean BW and GA, a higher incidence of severe respiratory distress symptoms, perinatal infection, use of surfactant, and need for FFP transfusion. However, multivariable logistic regression analysis showed that only FFP transfusion remained an independent risk factor for hsPDA (adjusted odds ratio = 3.880, 95% confidence interval: 1.214–12.402, p = 0.022) after adjusting for confounding factors.Conclusion FFP transfusion is a significant risk factor for the subsequent development of hsPDA in our study population. FFP transfusion may complicate the fluid management of premature infants and increase the risk of hsPDA.Key Points
Keywords: FFP transfusion; premature infants; hemodynamically significant PDA; intraventricular hemorrhage